On the solutions of electrohydrodynamic flow with fractional differential equations by reproducing kernel method - Akgul, Ali; Baleanu, Dumitru; İnç, Mustafa; Tchier, Fairouz (De Gruyter Open Ltd, 2016)
In this manuscript we investigate electrodynamic flow. For several values of the intimate parameters we proved that the approximate solution depends on a reproducing kernel model. Obtained results prove that the reproducing kernel method (RKM) is very effective. We obtain good results without any transformation or discretization. Numerical experiments on test examples show that our proposed schemes are of high accuracy and strongly support the theoretical results.
Keywords: kernel functions; electrohydrodynamic flow; approximate solutions